(n+2)(n+12)=0

Simple and best practice solution for (n+2)(n+12)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (n+2)(n+12)=0 equation:


Simplifying
(n + 2)(n + 12) = 0

Reorder the terms:
(2 + n)(n + 12) = 0

Reorder the terms:
(2 + n)(12 + n) = 0

Multiply (2 + n) * (12 + n)
(2(12 + n) + n(12 + n)) = 0
((12 * 2 + n * 2) + n(12 + n)) = 0
((24 + 2n) + n(12 + n)) = 0
(24 + 2n + (12 * n + n * n)) = 0
(24 + 2n + (12n + n2)) = 0

Combine like terms: 2n + 12n = 14n
(24 + 14n + n2) = 0

Solving
24 + 14n + n2 = 0

Solving for variable 'n'.

Factor a trinomial.
(12 + n)(2 + n) = 0

Subproblem 1

Set the factor '(12 + n)' equal to zero and attempt to solve: Simplifying 12 + n = 0 Solving 12 + n = 0 Move all terms containing n to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + n = 0 + -12 Combine like terms: 12 + -12 = 0 0 + n = 0 + -12 n = 0 + -12 Combine like terms: 0 + -12 = -12 n = -12 Simplifying n = -12

Subproblem 2

Set the factor '(2 + n)' equal to zero and attempt to solve: Simplifying 2 + n = 0 Solving 2 + n = 0 Move all terms containing n to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + n = 0 + -2 Combine like terms: 2 + -2 = 0 0 + n = 0 + -2 n = 0 + -2 Combine like terms: 0 + -2 = -2 n = -2 Simplifying n = -2

Solution

n = {-12, -2}

See similar equations:

| y=x*x+2 | | 3=2.1+4b+6 | | 6g=198 | | 21=10a+4b | | 12(x)(.5)=60 | | (a-5)(a+7)=0 | | 9=10a+4b+12 | | 3x+1=18+18x | | 24a-22=-2(1-6a) | | 3/4x1/2=4 | | -2x=-x-2 | | 20+10x=44+21x+9 | | 6(4c-10)+7(c-1)= | | 3x(2x-3y)= | | 3x*2=x | | x/7-3/14=1/7 | | n^3-n=0 | | 110000=x+.58*x | | 4x-y=31 | | 10a^2-20a^3=0 | | 5x^2-x^3=0 | | 4t+9=-9t+13 | | 2x+14y=28 | | 7(r-3)=21 | | -5s+4p=tp-4 | | 10p-8=8(6p-5)+10(2+4p) | | tgx/4=1 | | 65047/37262.665 | | 62(1+2)=x | | x^3=8/343 | | 6j-17=3j+13 | | 10p-8=-8(6p-5)+10(2+4p) |

Equations solver categories